CRÔNICA E AUTOFICÇÃO EM JOSÉ CARLOS OLIVEIRA - Bednarchuk, Francine Mariê Alves Higashi (2017)
This dissertation aims at analyzing the novel O pavão desiludido, published in 1972, by José Carlos Oliveira, regarding its autofiction. The novel was published in the writer's maturity, however it is a childhood-themed narrative strongly loaded of a presence of self-writing, which brings it closer to the genre proposed by Serge Doubrovsky (1977). Autofiction, a genre that mixes fiction and autobiography, and which has been increasingly discussed, gains strength in this novel by José Carlos Oliveira, prior to the very concept of the term. For this research, we go through Crônica, a typical Brazilian genre that helped in the formation of our literature, and which was much used by the author from the 1960s until his death in 1986. We also consider the analysis of the writer's intimate diary in order to understand the mirrored selves that constitute his fiction.